Rapid identification of Campylobacter pylori (C. pyloridis) by preformed enzymes. - McNulty, C A (1987)
Campylobacter pylori (C. pyloridis) is a fastidious organism found in the gastric mucosa associated with histological gastritis and peptic ulceration. A rapid identification scheme that detects the presence of preformed enzymes (Rosco Diagnostica, Taastrup, Denmark) was applied to clinical isolates of C. pylori. The isolates tested were a very homogeneous group. They all produced oxidase, catalase, urease, alkaline phosphatase, gamma-glutamyl aminopeptidase, leucine aminopeptidase, and DNase. None produced any of 44 other enzymes tested. No other campylobacter strains produced gamma-glutamyl aminopeptidase, except the six strains of Campylobacter jejuni biotype 2. Different results were obtained with similar substrates produced by other manufacturers, probably due to small substrate differences. These tests are useful for the rapid identification of C. pylori but would be unhelpful in any biotyping scheme. They can also be used to help differentiate other groups within the genus Campylobacter.